Manifestation of Tectonic and Climatic Perturbations in Deep-Time Stratigraphy – An Example From the Paleocene Succession Offshore Western Norway - Sømme, Tor Oftedal; Skogseid, Jakob; Embry, Patricia; Løseth, Helge (Frontiers in Earth Science, 2019)
Sediment routing systems may be subjected to different external controls that can modulate long and short-term sediment delivery to nearby basins. Here we investigate a Paleocene depositional system offshore western Norway that was subjected to long-term (~10 Myrs) tectonic perturbation and significant hinterland erosion. Superimposed on this long-term uplift, the system was also subjected to a short-lived climatic perturbation, which lasted ~200 Kyrs. Regional 3D seismic reflection data is integrated with high resolution well and biostratigraphic data to map the stratigraphic responses to these different scales of perturbations on the Paleocene system. The initiation of the tectonic perturbation is marked by an angular unconformity in seismic data. A rapid increase in sediment flux followed, causing initial progradation of a shelf-slope wedge. Calculations indicate that the tectonic uplift caused an order of magnitude increase in sediment flux to the basin, which peaked in the latest Paleocene. This period coincided with the Paleocene-Eocene Thermal Maximum (PETM), which is documented by biostratigraphic data as a discrete event within the overall regressive system. Although the PETM often is characterised by increased continental runoff, no increase in sediment supply can be demonstrated from seismic data. This study shows that the system response to tectonic perturbations may vary along strike, depending on the size of the routing systems and the antecedent topography prior to hinterland uplift. A low supply system may produce a tectonically-linked wedge that is of similar thickness as a climatically-linked wedge in a high supply system. This study documents how the same routing system responded to perturbations operating at different spatial and temporal scales and may help recognise similar process-response relationships in other areas.